A case study on the image projected by the U.P. Concert Chorus. - Inocencio, Ma. Katherine Reyes 1960-
This paper is an in-depth study of the UPCC. This paper focuses on three basic questions : What is the U.P. Concert Chorus? What is the UPCC's image as perceived by its members, and is such an image in consonance with the audiences' perception of the UPCC image? Lastly, how effective is the dissemination of information on the U.P. Concert Chorus?